2022
DOI: 10.33448/rsd-v11i13.35918
|View full text |Cite
|
Sign up to set email alerts
|

A Epidemiologia e as Ciências forenses

Abstract: A Epidemiologia Forense une os princípios e técnicas da epidemiologia e as ciências forenses e possibilita o preenchimento de lacunas entre questões jurídicas que envolvam situações clínicas (saúde-doença) e epidemiológicas, estabelecendo o nexo causal em ações civis e processos criminais e defesa. O objetivo deste trabalho foi fornecer uma breve revisão geral dos métodos e aplicações da epidemiologia forense, pois a epidemiologia forense é de interesse para aqueles que trabalham e estudam nas áreas de medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Carneiro & Botteon (2021) present an epidemiological overview of homicides in Brazil from the perspective of bloodstain analysis, exemplifying through some case studies that it was possible to establish the victim's positioning elements, movements that were performed, whether the scene was changed and even the authorship of the crime. Epidemiological studies can be of great value to forensic sciences in general, as Leite (2022) concluded that the following areas can be covered: Forensic Toxicology in knowledge should be aggregated and applied in the reasoning of the bloodstain analysis.…”
Section: Mamedesmentioning
confidence: 99%
“…Carneiro & Botteon (2021) present an epidemiological overview of homicides in Brazil from the perspective of bloodstain analysis, exemplifying through some case studies that it was possible to establish the victim's positioning elements, movements that were performed, whether the scene was changed and even the authorship of the crime. Epidemiological studies can be of great value to forensic sciences in general, as Leite (2022) concluded that the following areas can be covered: Forensic Toxicology in knowledge should be aggregated and applied in the reasoning of the bloodstain analysis.…”
Section: Mamedesmentioning
confidence: 99%